Analisis Tingkat Kepuasan Pelanggan dengan Menerapkan Algoritma C4.5 - Reza Fauzy; Riki Winanjaya; Susiani (Bulletin of Computer Science Research, 2022)
Furniture is currently a secondary item that is quite needed among the community to support their daily activities. In its use, furniture becomes an item that really helps human activities in their daily lives. But now furniture marketing is not only in terms of use, but now people have their own assessment of the aesthetic value of a furniture. So this is a demand for furniture business people to make variations on each product to be marketed. Customer satisfaction is one of the most important things in assessing the level of service provided by the company to its customers. The purpose of this study was to determine the level of satisfaction of CV. Karinda customers. at the company CV. This aspect of Karinda has not been measured, so CV. Karinda finds it difficult to determine which aspects must be improved. The method used in this study is the C 4.5 algorithm, where the data source used is a questionnaire/questionnaire technique given to CV. Karinda customers. the process of testing this research using RapidMinner software to create a decision tree. From the results of the analysis is expected to improve the company's performance in providing services to customers CV. Karinda to be better